EFFECT OF THE FORCES ON THE SEPARATION OF FIBER FLOW FROM THE SAW IN AN IMPROVED LOWER FIBER REMOVAL DEVICE - Mirzaumidov, Asilbek; Ganikhanov, Khasankhon; Mavlyanov, Aybek; Abdusamatov, Alisher (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In the article is presented an analysis of a fiber bottom stripping device in the cotton gin industry that allows increased airflow rate, consumes less air and improves the efficiency of stripping fibers from saw teeth of the saw cylinder. The effects of forces in isolating the fiber stream from the saw have been studied.